Two new Bdellidae (Trombidiformes: Bdelloidea) from Iran and the status of Neobiscirus Gomelauri, 1963 - Paktinat-Saeej, Saeed; Bagheri, Mohammad; Saboori, Alireza; Ahaniazad, Mansoureh (Zootaxa, 2015)
Two new Bdellidae, Biscirus iranensis Paktinat-Saeej & Bagheri sp. nov. and Bdella farabii Paktinat-Saeej & Bagheri sp. nov., are described from northern Iran. The monotypic genus Neobiscirus considered a junior synonym of Biscirus, and its only species therefore considered Biscirus kobachidzei (Gomelauri, 1963) comb. nov.